Racial/ethnic differences in the relationship between wealth and health across young adulthood. (March 2023) - Sun, Sicong; Lee, Hedwig; Hudson, Darrell L.
Abstract: Background: Although the relationship between socioeconomic position (SEP) and health has been well documented, very few prior investigations have examined the time-varying association between wealth and health across race/ethnicity. This study examined the racial/ethnic differences in the wealth–health associations during young adulthood. Method: Data were drawn from the National Longitudinal Survey of Youth 1997 with three time points, when respondents were aged 20, 25, and 30. The primary dependent variable was dichotomized self-rated health (SRH). Two indices of wealth were calculated: respondents' own reported net worth and reported parental net worth in 1997. Other SEP indicators included household income, education, employment status, and parental education. Three racial/ethnic groups were examined: nonHispanic White, non-Hispanic Black, and Hispanic. Two-level logistic regression was performed, stratified by race/ethnicity. Results: In the whole-sample analysis, racial/ethnic differences in SRH were not statistically significant, after controlling for wealth. For self-reported net worth during young adulthood, wealth has a incremental consistent effect on health among non-Hispanic White respondents and Hispanic respondents but not among Black respondents. Individual net worth and parental net worth were only significantly associated with health among the highest wealth quartiles among non-Hispanic Black respondents. Only individual net worth, not parental net worth, was significantly associated with SRH in the Hispanic sample. Conclusion: This study examined racial/ethnic differences in time-varying relationship between wealth and health during young adulthood. Findings indicate that there are notable racial/ethnic differences in the patterning of wealth–health association that appear to emerge in early adulthood. Implications for asset-based policy and programs are discussed. Highlights: Wealth attenuated racial differences in self-rated health during young adulthood. Wealth had consistent incremental effect on health among White & Hispanic Americans. For Black Americans, wealth was protective of health in the highest wealth quartile. Individual wealth, not parental wealth was associated with health among Hispanics.